L2 comprehension of filled pauses and fillers in unscripted speech. (April 2022) - Carney, Nathaniel
Abstract: One ubiquitous feature of unscripted speech across languages is the use of filled pauses and fillers. However, research has hitherto yielded opposing or ambiguous results about whether filled pauses and fillers in spontaneous speech aid or hinder L2 listeners' comprehension. In the current study, 30 L1 Japanese participants of three English proficiency levels viewed two video texts spoken by two different speakers of General American English. The video texts contained four occurrences of the filled pause um and two occurrences of the filler like. Participants had multiple opportunities to view and comprehend the texts. Comprehension, decoding, and internal processing of the video texts were elicited through a three-task assessment procedure of L1 recalls, L2 repetitions, and verbal reports. Results revealed that some occurrences of um and like caused comprehension difficulties for most participants while other occurrences caused no noticeable difficulty for any participants. The findings suggest that the location of filled pauses and fillers, L2 listeners' language proficiency, and multiple other factors can determine whether or not filled pauses and fillers will affect L2 listening comprehension of spontaneous speech.